Structure and strength of biocompatible coatings for titanium nickelide obtained in different reaction atmospheres - Dubovikov, Kirill M.; Garin, Alexander S.; Shishelova, Arina A.; Kovaleva, Marina A. (Non-ferrous metals)
The three layers Ti/Ni/Ti amorphous nanolaminate was applied to the TiNi substrate by magnetron sputtering. But subsequent synthesis provided in nitrogen and argon-nitrogen-carbonium dioxide atmospheres changed their phase composition and structure. The coating synthesized in nitrogen atmosphere consists mostly of the titanium nitrides but not from titanium oxides which were formed during synthesis in argon-nitrogen-carbonium dioxide atmosphere. Despite the fact that the nitrides have great hardness the scratch tests showed the coating synthesized in argon-nitrogencarbonium dioxide atmosphere has better adhesion to the substrate. The load of 30 N is not enough for complete delamination of the coating. The results obtained with the aid of tensile tests demonstrated that the coating thickness less than 250 nm does not affect significantly on martensitic deformation of the TiNi phase.